A taxonomic account of Myrciinae (Myrteae, Myrtaceae): generic and sectional placement of forgotten species and a list of all accepted species - Santos, Matheus F.; Amorim, Bruno S.; Burton, George P.; Faria, Jair E.q.; Fernandes, Thiago; Flickinger, Jonathan A.; Gaem, Paulo Henrique; Landrum, Leslie R.; Lima, Duane F.; Proença, Carolyn E.b.; Rosa, Priscila O.; Lima-Dos-Santos, Leidiana; et al. (Phytotaxa, 2024)
The taxonomy of Neotropical Myrtaceae is known for the difficulties regarding specific and supraspecific taxonomic delimitations. In subtribe Myrciinae (tribe Myrteae) this situation is intensified due to the high diversity of species and relatively homogeneous morphology. Over the last two decades there has been a huge increase in Myrciinae systematic research. Following use of molecular phylogenetic works, several genera accepted in the 20th century were synonymised under a broader circumscription of Myrcia. Monophyletic sections that facilitated further taxonomic works were recognised. However, species with doubtful morphologies, scanty or missing data have remained untreated. This paper provides an update of the taxonomic status of these species as well as a list of accepted species of Myrciinae, assigned to sections of Myrcia. This work is based on a broad analysis of herbarium collections including types and the Myrciinae literature. Taxonomic comments are provided regarding species placement and features, and three new combinations, one new name, nine lectotypifications and two neotypifications are provided. Seven species are transferred to other genera or families. Thirty-seven species are listed as incompletely known due to absence of type specimens or any material that could clarify their taxonomic status. We currently accept 744 species of Myrcia (excluding the 37 species without known type collections and three species with uncertain generic placement), distributed between taxonomic sections as follows: Myrcia sect. Aguava (32 species), Myrcia sect. Aulomyrcia (162 species), Myrcia sect. Calyptranthes (248 species), Myrcia sect. Eugeniopsis (18 species), Myrcia sect. Gomidesia (67 species), Myrcia sect. Myrcia (158 species), Myrcia sect. Reticulosae (15 species), Myrcia sect. Sympodiomyrcia (28 species), Myrcia sect. Tomentosae (5 species), and clade 10 with nine species. Three species remain in Myrcia but are probably members of other taxa of Myrteae (M. cionei, M. skortzoviana) or other family (M. melastomoides), while two species of Myrcia (M. apiocarpa, M. sintenisiana) remain without a sectional placement. We highlight taxonomic issues to address in the future to improve systematic knowledge in Myrciinae.